Storage lipids and proteins of Euterpe edulis seeds - Panza, Victor; Pighin, Darío Gabriel; Láinez, Verónica; Pollero, Ricardo José; Maldonado, Sara (Sociedad Latinoamericana de Microscopía Electrónica y Centro Regional de Investigaciones Científicas y Tecnológicas (Mendoza, Argentina), 2022)
Comparative studies on fatty acid and protein composition of the endosperm and embryo of palmito (Euterpe edulis Martius) were conducted using gas-liquid chromatography and sodium dodecyl sulfate– polyacrylamide gel electrophoresis. On a dry weight basis, the embryo contained extremely lower amounts of lipids and proteins than did the endosperm, which was associated with the scarce lipid and protein bodies previously reported in axis and cotyledon. The fatty acid composition also exhibited differences between both tissues: (I) the fatty acid diversity was greater in embryo than in endosperm; (II) embryo and endosperm contained predominantly linoleic, palmitic, oleic and stearic acids even though the relative values were different for each tissue. As compared to other palm species, the higher fatty acid unsaturation in Euterpe edulis seed could be involved in the previously reported short longevity and recalcitrant behavior during storage. Proteins of both tissues were heterogeneous in molecular mass. Some proteins were tissue-specific, but other were common, among them a highly glycosylated protein which migrated at about 55 kDa. We hypothesize that the latter, also reported in all previously studied palm species, is one of the proteins characterizing the Arecaceae family.